IMPORTANCE OF COMMUNICATION IN ORGANIZATIONAL INTELLIGENCE DEVELOPMENT IN THE CONTEXT OF GLOBAL CRISIS - MANOELA POPESCU (Challenges of the Knowledge Society)
It is now clear that different ways to generate, integrate and apply knowledge within organizations varies accordingly, at least, with the human factor, regardless privileged modalities of interactions between the firm and the environment. In the current context, of the global economic crisis, communication and communicative behavior are sometimes improperly used in explaining institutional deficits. However, the role of communication in generating the appearance and development of intelligence organizational context (organizational context, technological and linguistic) and at the determinants and co-factors of organizational intelligence (organizational learning, leadership, organizational culture, management) is major. Besides that, generating knowledge in organizational framework is achieved through communication.